2013
DOI: 10.1007/978-1-4614-7411-1_55
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pulse Oximetry Accuracy by Removing Motion Artifacts from Photoplethysmograms Using Relative Sensor Motion: A Preliminary Study

Abstract: To expand applicability of pulse oximetry in low-acuity ambulatory settings, the impact of motion on extracted parameters as saturation (SpO 2 ) and pulse rate (PR) needs to be reduced. It is hypothesized that sensor motion relative to the skin can be used as an artifact reference in a correlation canceler to reduce motion artifacts in photoplethysmograms (PPGs), in order to improve SpO 2 and PR measurements. This has been proven true in in-vivo measurements, where forehead PPGs have been obtained while subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Several companies have developed techniques for the elimination of motion artifacts in pulse oximeters, and since the subject has been reviewed and discussed in several articles,7,30,66,67 it is not discussed in this review. Motion rejection is generally achieved using various algorithms for differentiation between pure PPG signals and those contaminated by motion noise, but also through the introduction of improved hardware.…”
Section: Limitations Of Pulse Oximetry and Technological Updatementioning
confidence: 99%
“…Several companies have developed techniques for the elimination of motion artifacts in pulse oximeters, and since the subject has been reviewed and discussed in several articles,7,30,66,67 it is not discussed in this review. Motion rejection is generally achieved using various algorithms for differentiation between pure PPG signals and those contaminated by motion noise, but also through the introduction of improved hardware.…”
Section: Limitations Of Pulse Oximetry and Technological Updatementioning
confidence: 99%
“…This technology is now in widespread use in health watches for fitness consumer applications. Besides this technical progress we showed in pre-clinical CPR studies under controlled conditions [12,13] that PPG appears to have the potential to indicate when the heart resumes beating and should therefore be reconsidered as a tool in CPR decision support.…”
Section: Introductionmentioning
confidence: 94%
“…Prior research by some of the authors of this investigation has demonstrated promising application of a custom designed PPG sensor device in monitoring heart rate (HR), oxygen saturation (SpO 2 ) and total haemoglobin concentration (Hb) [3,4]. However, a drawback of this technology has been that the PPG signal is easily affected by motion artifact [5,6,7,8,9,10,11], requiring the subject (patient) to be motionless and lying or sitting down.…”
Section: Introductionmentioning
confidence: 99%
“…proposed finger motion in five different positions, e.g., horizontal movement of finger and waving hand [5], and Peng et al studied four types of finger motion, such as bending and pressing of the finger [6]. Methods used to minimize the impact of motion artefact include: adaptive noise cancellation algorithms (e.g., normalized least-mean-square) to recover signals corrupted due to body motion using acceleration data [7,8], relative sensor motion via self-mixing interferometry in a laser diode [9], periodic moving average filter [10], a method that uses synthetic noise reference signal without any extra hardware [11], etc.…”
Section: Introductionmentioning
confidence: 99%